The Transformation of Da‘wah Communication Patterns among Religious Guides of Persatuan Islam - Anggit Garnita; Mu'minatul Zanah (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2025)
The purpose of the discussion on the transformation of da‘wah communication patterns among religious guides of Persatuan Islam is to examine Persis as a da‘wah organization in which shifts have occurred in the ways da‘wah messages are delivered. These shifts are influenced by various underlying factors affecting Persis religious guides in the process of da‘wah transformation. This phenomenon is analyzed using Everett M. Rogers’ Diffusion of Innovations theory, which includes the construction of innovation, the use of communication channels, the innovation decision-making process, and the social system related to the achievement of goals. This study aims to describe the construction of transformed communication patterns among Persis preachers based on their own understanding and experiences. This research employs a qualitative approach using a phenomenological method. The method is expected to provide a comprehensive depiction of the transformation of communication patterns among religious guides of Persatuan Islam. Data collection techniques include observation and in-depth interviews. Based on the findings of the study, it can be concluded that a transformation in communication patterns has occurred among Persatuan Islam religious guides, encompassing both content and rhetorical dimensions. Previously, da‘wah activities conducted by Persatuan Islam religious guides were oriented toward fiqh-based studies. Over time, however, the content of da‘wah has transformed in accordance with evolving social issues. Transformation has also taken place in the rhetorical dimension. Whereas the earlier approach was agitational, rigid, and polemical, in the era of globalization Persatuan Islam religious guides now employ adaptive and persuasive communication approaches in their da‘wah activities.